Cecropia Moth, Cecropia Silk Moth, Robin Moth, Hyalophora cecropia Linnaeus (Insecta: Lepidoptera: Saturniidae: Saturniinae: Attacini) - Geoffrey R. Gallice (EDIS)
EENY 478, a 5-page illustrated fact sheet by Geoffrey R. Gallice, is part of the Featured Creatures collection. It describes this spectacular member of the Saturniidae family — synonymy, distribution, hosts, and economic importance. Includes references. Published by the UF Department of Entomology and Nematology, July 2010.